Purification of waste engine oil using raw clay, acid treated clay and clay/activated charcoal (Journal of Bangladesh Academy of Sciences, 2024)
The purification of waste engine oil was conducted utilizing locally available clay in three different forms: raw, acid-treated, and a mixture of clay with activated charcoal. A 72.6% and 70.12% purification efficiency has been achieved when employing raw and acid-treated clay, respectively. However, the purification yield decreased to 64.35% when utilizing a combination of acid-treated clay and activated charcoal. FTIR analysis confirmed the presence of alkanes and alkenes in the purified oil. The NMR and GC-MS analysis identified the presence of linear and branched alkanes and alkenes, as well as substituted-benzene compounds in the purified oil. The density of waste engine oil and the corresponding purified oil was determined to be 0.929 g/mL and 0.825 g/mL, respectively. After purification, the kinematic viscosity decreased from 192 mm2/sec to 70 mm2/sec at 40 °C. The AAS analysis revealed the presence of 13.28 mg/L of lead (Pb) and 91.56 mg/L of chromium (Cr) in the waste engine oil, which significantly decreased to 0.02 mg/L and 0.037 mg/L, respectively, after purification with clay mixed with activated charcoal.J. Bangladesh Acad. Sci. 48(1); 121-134: June 2024